2021
DOI: 10.1002/plr2.20140
|View full text |Cite
|
Sign up to set email alerts
|

‘VT Sweet’: A vegetable soybean cultivar for commercial edamame production in the mid‐Atlantic USA

Abstract: Commercially viable cultivars adapted to U.S. production regions that meet consumer acceptance criteria are desperately needed by the growing domestic edamame industry. Here, we report the development and release of 'VT Sweet' (Reg. no. CV-542, PI 699062), the first vegetable soybean [Glycine max (L.) Merr.] cultivar released by Virginia Tech. VT Sweet is a late maturity group (MG) V cultivar (relative maturity 5.6, 129 d to harvest) with determinate growth habit, purple flowers, gray pubescence, tan pod wall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The three "sweet" accessions characterized in present study had the comparable sucrose content but significantly high Ala content. By contrast, VT Sweet, a recent released edamame cultivar (Zhang et al, 2021), had 69.22 ± 21.65 mg sucrose g -1 fresh bean and 0.59 ± 0.07 mg Ala g -1 fresh bean in the Blacksburg extension trial, 2019. PI532469 and PI243551 both originated from Japan and PI407748 originated from China.…”
Section: Potential Edamame Breeding Pismentioning
confidence: 94%
“…The three "sweet" accessions characterized in present study had the comparable sucrose content but significantly high Ala content. By contrast, VT Sweet, a recent released edamame cultivar (Zhang et al, 2021), had 69.22 ± 21.65 mg sucrose g -1 fresh bean and 0.59 ± 0.07 mg Ala g -1 fresh bean in the Blacksburg extension trial, 2019. PI532469 and PI243551 both originated from Japan and PI407748 originated from China.…”
Section: Potential Edamame Breeding Pismentioning
confidence: 94%
“…To achieve this goal, we applied Oxford Nanopore Long-Read Sequencing Technology (ONT) to sequence 28 representative genotypes of both grain-type soybean and vegetable soybean (edamame) as well as the reference variety, William 82 (W82, Table S1). This germplasm compilation includes grain-type soybeans such as Hutcheson and V12-4590 used in livestock feeding, food-grade soybeans like zizuka (natto), V10-3653 (soy milk and tofu producing variety), MFS-561 (sprout variety), and vegetable soybeans (edamame) including VT-Sweet and V16-0565 9-12 . These genotypes feature diverse traits such as high methionine content, high yield, varying seed protein levels, distinct plant heights (both high and low), and high oleic acid content, and different seed weights (Figure 1 and Table S1).Our study doubled the number of soybean genotypes that were re-sequenced by a long-reading sequencing approach 4 .…”
Section: Mainmentioning
confidence: 99%
“…Vegetable soybeans are harvested at the R6 stage, when the pods are green and the seeds are full [2] . Research has reported that the pods size, including large pods and grains, is an important visual quality unique to vegetable soybeans [3,4]. Therefore, the size of vegetable soybean pods has been considered to be one of the most important traits in accelerating the breeding process of vegetable soybean.…”
Section: Introductionmentioning
confidence: 99%